Dendrimer‐Based, High‐Luminescence Conjugated Microporous Polymer Films for Highly Sensitive and Selective Volatile Organic Compound Sensor Arrays. (14th February 2020) - Liu, Huaqian; Wang, You; Mo, Wanqi; Tang, Hongliang; Cheng, Zhiyong; Chen, Yu; Zhang, Shitong; Ma, Hongwei; Li, Bin; Li, Xiaobai
Abstract: Conjugated microporous polymers (CMPs) are attracting increasing attention in chemical sensing due to their extended π‐conjugated framework, permanent microporous structure, and large specific surface area. However, the extremely poor solubility and processability of CMPs, as well as the serious fluorescence quenching caused by aggregation, restrict their practical applications. Herein, a high‐luminescence CMP film is constructed based on a novel dendrimer (TPETCz) featured by its central tetraphenylethylene "core" with aggregation‐induced emission effect and its highly electro‐active "branches." High specific surface area CMP films for analyte diffusion are fabricated by a facile in situ electropolymerization method. These dendrimer‐based CMP films exhibit superior sensitivity to volatile organic compounds (VOCs). More importantly, 18 types, the most types reported, of VOC vapors are precisely distinguished by the linear discriminant analysis by establishing a 2D fluorescence sensor array based on the CMP films and the dendrimer monomer films. Abstract : Based on the dendrimers with aggregation‐induced emission features, a high‐luminescence conjugated microporous polymer (CMP) film is fabricated using a simple and feasible electrochemical polymerization method. Further, a 2D fluorescence sensor array, which consists of CMP films and monomer spin‐coated films, is built, and 18 types, the most types reported, of volatile organic compound vapors are precisely distinguished.